Social defeat stimulates local glucocorticoid regeneration in lymphoid organs - Ergang, Peter; Mikulecká, Anna; Vodicˇka, Martin; Vagnerová, Karla; Mikšík, Ivan; Pácha, Jirˇí (Endocrine connections, 2018)
Stress is an important risk factors for human diseases. It activates the hypothalamic-pituitary-adrenal (HPA) axis and increases plasma glucocorticoids, which are powerful regulators of immune system. The response of the target cells to glucocorticoids depends not only on the plasma concentrations of cortisol and corticosterone but also on their local metabolism. This metabolism is catalyzed by 11β-hydroxysteroid dehydrogenases type 1 and 2, which interconvert glucocorticoid hormones cortisol and corticosterone and their 11-oxo metabolites cortisone and 11-dehydrocorticosterone. The goal of this study was to determine whether stress modulates glucocorticoid metabolism within lymphoid organs - the structures where immune cells undergo development and activation. Using the resident-intruder paradigm, we studied the effect of social stress on glucocorticoid metabolism in primary and secondary lymphoid organs of Fisher 344 (F344) and Lewis (LEW) rats, which exhibit marked differences in their HPA axis response to social stressors and inflammation. We show that repeated social defeat increased the regeneration of corticosterone from 11-dehydrocorticosterone in the thymus, spleen and mesenteric lymphatic nodes (MLN). Compared with the F344 strain, LEW rats showed higher corticosterone regeneration in splenocytes of unstressed rats and in thymic and MLN mobile cells after stress but corticosterone regeneration in the stroma of all lymphoid organs was similar in both strains. Inactivation of corticosterone to 11-dehydrocorticosterone was found only in the stroma of lymphoid organs but not in mobile lymphoid cells and was not upregulated by stress. Together, our findings demonstrate the tissue- and strain-dependent regeneration of glucocorticoids following social stress.
Keywords: Fisher 344 rats; Lewis rats; social stress; resident-intruder paradigm; glucocorticoid metabolism; lymphoid organs